Investigation of the role of human parvovirus B19 in chronic anaemia of HIV infected TB patients - Van Niekerk, Albertus Bernhardus Willer (My University, 1994)
This study was undertaken to determine the role of human parvovirus B19 (B19) in chronic anaemia of HIV infected TB patients. Patlents were selected from an existing databank of 307 patients included ln a MRC HIV/TB study. Twenty-nine patients, 15 colnfected with HIV/TB and 14 Infected with TB only, were identified for further evaluation. These patients' sera were subjected to serological and DNA detection studies using IgG and IgM ELISA methods and a nested polymerase chain reaction (PCR) assay. The selection of the nested PCR was based on comparative evaluation of a new rapid 99 cycle PCR method recommended for hepatitis B DNA detection and the nested PCR method established for B19. The nested assay was shown to be the more sensitive system in the context of B19 DNA detection. Serological evaluation of these 29 patients suggested that a greater proportion of HIV/TB patients with chronic anaemia had evidence of recent or past exposure to B19 than those not experiencing anaemia. The nested PCR demonstrated the presence of circulating B19 DNA in 2 coinfected individuals with haematological pictures compatible with persistent B19 infection. B19 DNA was also demonstrated in a TB only patient without anaemia; further haematological and serological evidence in this patient suggested recent exposure to B19. The serological and DNA amplification assay results of these 29 patients would suggest a possible role - either causal or co-factorial - for persistent B19 infection in the establishment of chronic anaemia in HIV/TB patients.
A dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, in partial fulfilment of the requirements for the degree Master of Medicine (Virology)
Keywords: Parvovirus B19, Human.; Parvoviridae Infections.